Analysis of the physical characteristics of losartana potassium 50mg tablets dispensed in a Basic Health Unit and in drugstores in the city of Abaetetuba-PA (Research, Society and Development, 2021)
Systemic Arterial Hypertension (SAH) is a multifactorial clinical condition characterized by sustained elevation of blood pressure levels ≥ 140 systolic and/or 90 diastolic mmHg. Consequently, for treatment and control of the disease, losartan potassium 50 mg is an antihypertensive widely used by the population. Therefore, the present article aims to identify possible quality deviations in losartana potassium 50mg tablets dispensed in a basic health unit and drugstores in the city of Abaetetuba-PA. In order to achieve the objective, analysis visual identification, average weight and friability were performed in order to compare with the Brazilian Pharmacopoeia and identify possible non-conformities. The results obtained in the visual analysis were normal parameters of color, odor and integrity of the tablets and packaging. In the average weight test the results were variations of 1.32% in similar pills, 1.64% in generic pills, and 1.02% in reference pills. In the friability test the maximum loss reached was the similar tablets with 0.13%, and the minimum was the reference tablets with 0.1%. Thus, the results showed a profile compatible with that established in the Brazilian Pharmacopoeia, with variation percentages within the established limit. Thus, it is concluded that losartana potassium 50mg tablets dispensed in the city have quality, thus ensuring the effective treatment of patients suffering from SAH.